Thermodynamic Pathways and Phase Equilibria in the Si-C-O System Insights from Ellingham and TPP Diagrams - Baigenzhenov, Omirserik; Temirgali, Ingkar; Turan, Mehmet Deniz; Maldybayev, Galymzhan; Sharipov, Rustam; Kusiorowski, Robert; Hosseini-Bandegharaei, Ahmad (Sami Publishing Co-Spc, 2026)
This work presents a thermodynamic investigation of the silicon- carbon-oxygen (Si-C-O) system aimed at optimizing the carbothermic reduction of silica for industrial production of silicon. Ellingham and thermodynamic predominance phase (TPP) diagrams were constructed across a wide temperature range (1,227-2,227 degrees C; 1,500-2,500 K) to evaluate the stability and equilibrium of key phases. The results reveal a sequential reduction pathway originating with silicon carbide (SiC) formation at moderate temperatures, followed by gaseous silicon monoxide (SiO) and carbon monoxide (CO) as dominant intermediates, culminating in the stabilization of metallic silicon at elevated temperatures under strongly reducing conditions. The Ellingham analysis confirms the broad thermodynamic favorability of SiC formation, while free silicon becomes stable only above approximately 1,800-2,200 degrees C (2,073-2,473 K), depending on system openness. TPP diagrams highlight the crucial role of gas-phase transport phenomena and charge composition in phase equilibria, with gas retention strategies proving essential to maximize silicon yield. Comparative evaluations with existing literature underscore the importance of optimizing carbon-toSiC ratios and controlling gas-phase composition to improve energy efficiency and process efficiency. This study offers vital thermodynamic insights for advancing silicon manufacturing technologies through precise control of temperature, gas species, and feedstock composition.
Keywords: Si-C-O system; Carbothermic reduction; Thermodynamic modelling; Ellingham diagram; Phase predominance diagram